Priorização da manutenção em subestações com foco na confiabilidade e na remuneração da função transmissão - Vianna, Elaine Aparecida de Lima (2016)
Transmission companies, in Brazilian electricity sector, are paid by the facilities available to the National Interconnected System - SIN. The different equipment on the transmission system are subject to the occurrence of defects, which can result in failure and may result in outages and / or operational constraints. These occurrences cause the application of a penalty, called Variable Portion, consisting of a discount in the amount of remuneration is provided. This thesis aims to support maintenance planning, aiming at the reduction of Variable Portions and of the negative financial impact caused by this penalty, by a new methodology to define a priority scale for maintenance actions in substations, based on the development of a Composite Risk Index (CRI) associated with each device. Two auxiliary indices are built: Basic Condition (BC) and Operating Condition (OC), representing the physical and functional characteristics of the equipment that can compromise their performance and contribute to the occurrence of failures. Their evaluation is helped by a Technical Capacity Index (TCI), which evaluates how much the equipment has been affected by wear and tear, in the assessment of the Basic Condition, and the classification of the equipment defects by degrees of severity, in the assessment of the Operating Condition. Two cascading Fuzzy Inference Systems of the Mandani type are used, the first in defining the BC, and the second to obtain the equipment CRI denoting maintenance priority, which may then be used in planning maintenance actions. The methodology is verified through an SF6 circuit breaker CRI assessment, and its priority scale for maintenance planning. The procedure for evaluating the SF6 circuit breakers reliability is evaluated through a comparison with a statistical approach, using real data collected from equipment installed in Eletrobras Eletronorte Transmission System, in Rondônia, Amazon region of Brazil.